Pelembagaan Konsep Pengendalian Hama Terpadu di Indonesia - Kasumbogo Untung (Jurnal Perlindungan Tanaman Indonesia, 2000)
Indonesia for a period of ten years (1989-1999) has trained more than one million farmers through a national programme of IPM Farmers' Field School especially on riceand other food crops. The success of farmers training based on participatory approach in Indonesia has been recognized globally as one of the pioneer of the Ecological Integrated Pest Management paradigm. The follow-up activities after the National IPM Programme which need to be done is to institutionalize IPM concept among government, industries and community institutions. Due to the presence of conflicts between ecological IPM paradigm and technological IPM paradigm which formally and legally supported by the government and the industry, processes of institutionalization of IPM in Indonesia will require a large efforts and funds, and take a long time.